The genus Toxoneura Macquart (Diptera, Pallopteridae) of the Oriental Region - Ozerov, A.l.; Krivosheina, M.g. (Zootaxa, 2019)
A new species of Toxoneura Macquart from Vietnam (Lai Châu province, Mt. Emei), T. gavryushini sp. n., is described and illustrated. This is the second species from the Oriental Region and the first species found in its continental part. The new species differs from other Oriental species, Toxoneura striata, in narrow gena and wing pattern. An identification key to the Oriental species is provided.